2014
DOI: 10.1128/aac.02418-13
|View full text |Cite
|
Sign up to set email alerts
|

Identification of CMY-2-Type Cephalosporinases in Clinical Isolates of Enterobacteriaceae by MALDI-TOF MS

Abstract: This study exploited the possibility to detect Citrobacter freundii-derived CMY-2-like cephalosporinases in Enterobacteriaceae clinical isolates using matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS). Periplasmic proteins were prepared using a modified sucrose method and analyzed by MALDI-TOF MS. A ca. 39,850-m/z peak, confirmed to represent a C. freundii-like ␤-lactamase by in-gel tryptic digestion followed by MALDI-TOF/TOF MS, was observed only in CMY-producing isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Gaibani et al demonstrated that the 11,109-Da peak was detected in 88.2% of the KPC producers, confirming previous results (94). Papagiannitsis et al described the identification of CMY-2 ␤-lactamases by detection of the mass peak at 39.850 Da by MALDI-TOF MS (95). The preparation of the sample involved a labor-intensive method with extraction of the periplasmic proteins performed by a modified sucrose method that lasts around 22 h. This group also performed some preliminary analyses for detection of ACC and DHA enzymes.…”
Section: Detection Of ␤-Lactamasesmentioning
confidence: 99%
“…Gaibani et al demonstrated that the 11,109-Da peak was detected in 88.2% of the KPC producers, confirming previous results (94). Papagiannitsis et al described the identification of CMY-2 ␤-lactamases by detection of the mass peak at 39.850 Da by MALDI-TOF MS (95). The preparation of the sample involved a labor-intensive method with extraction of the periplasmic proteins performed by a modified sucrose method that lasts around 22 h. This group also performed some preliminary analyses for detection of ACC and DHA enzymes.…”
Section: Detection Of ␤-Lactamasesmentioning
confidence: 99%
“…If bacteria are sensitive, the antibiotic spectra will not change. Appearance of the mass peak corresponding to the β ‐lactamase enzyme can be monitored, but it has only been described for ampicillin‐resistant Escherichia coli and for the identification of CMY‐2 β ‐lactamases . Besides, these methods that focus on the enzyme identification are much slower and more tedious to carry out in a clinical laboratory.…”
Section: Introductionmentioning
confidence: 99%
“…One approach to shorten the time to result for antibiotic susceptibility testing (AST) is the use of matrix-assisted laser desorption ionizationtime of flight mass spectrometry (MALDI-TOF MS) for identification and resistance testing. The most common approach using mass spectrometry is the detection of ␤-lactamases with a functional assay that measures their hydrolysis products (4)(5)(6)(7)(8)(9). This test provides results within 1 to 3 h, but, by its very nature, it is limited to the detection of ␤-lactamase-mediated resistance.…”
mentioning
confidence: 99%